Analisis Dampak Transformasi IAIN Menjadi UIN dan Strategi Terhadap Perkembangan Keilmuan Ekonomi Islam - Ghina Ulfa Saefurahman; Madnasir Madnasir; Yulistia Devi; M. Bahrudin; Rahmad Nur Wicaksono (Jurnal Ilmiah Ekonomi Islam, 2022)
Transformation in a university is absolute. Towards a better change in serving in the field of education for the community in order to create progress in Indonesian education that is balanced and in line with the times without leaving the Islamic identity of the university itself. By implementing a strategy to achieve the goal of becoming a World Class University for UIN Sunan Gunung Djati and an International Referral University for UIN Raden Intan Lampung. And one of these transformational changes is the development of Islamic economics which continues to thrive in society. So to deal with this, UIN presents an Islamic economics study program to produce human resources who have competence in this field. Providing a balanced lecture curriculum and creating graduates who have prospects in filling the field of sharia economics, sharia business practitioners, sharia finance practitioners, and halal industry practitioners.